Local knowledge on bird species and socio-economic cultural and ecology functions of birds and their various disturbances in the rural ecosystem of the Cisokan watershed, West Java - Juliati Prihatini; Sidik Permana; Johan Iskandar; Salma Rizkya Kinasih (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Actually in the past, rural people of West Java had in-depth local knowledge on various species of birds. Nowadays, the local people's knowledge on the bird species is being eroded due to the erosion of the local language and the bird population decreasing in the village ecosystem. The purpose of this study was to elucidate the knowledge of bird species, and the socio-economic, cultural, and ecological functions, and various disturbances to bird populations. The research was conducted in Bojongsalam and Sukaresmi Village, Rongga Sib-District, West Bandung, Cisokan Watershed, West Java. The method used in this study was a qualitative method, some techniques, including observation, participatory observation, and deep interview with informants were employed in this study to collect the primary data. The results showed that based on the local knowledge of the rural people, 74 species of birds were documented. The birds are classified by rural people based on body size, body feather color, type of habitat, and bird behavior. Bird species have an important role for socio-economic, cultural and ecological functions. Disturbance to bird populations, among others, due to the construction of the Cisokan hydropower project.